RETROSPECTIVE PLOT IN THE WORK OF ABDULLA KADIRI (ON THE EXAMPLE OF THE NOVEL “SCORPION FROM ALTAR”) (Scientific journal of the Fergana State University, 2024)
In this article, the retrospective type, uniqueness, content, and structure of the plot in the works of Abdulla Qodiriy, the forms of the retrospective part depending on who is using them, the elements of retrospection, and their functions in the literary work are explored, using the example of the novel “Scorpion from the Altar”.